CLIL methodology to develop reading skills. - Chiluisa Molina, Mónica Fernanda (2023)
The present research has as a general objective to analyze the effectiveness of the CLIL (Content and Language Integrated Learning) methodology in the development of the reading skills of students at the language center of the Vicente Leon Technologic Superior Institute at the B1 level. A group of 30 students was the population selected for this study. In addition, the researcher used quantitative and pre-experimental research, the instruments involved in data collection were the pretest, at the beginning of the proposal, and the posttest at the end of the application of the proposal. The reading section of the PET Cambridge test was used. During the classroom intervention, 5 workshops were developed based on CLIL methodology and reading strategies such as predicting answering questions, connecting, making inferences, and answering questions to develop reading comprehension strategies in the students. The analysis of the data was carried out using Student´s T test in the SPSS statistical program, which allowed to discard of the hypotheses by determining the existence of significant differences between the pretest and posttest. At the end of the project, students improved and achieved significant development in reading comprehension and vocabulary. The results revealed that the use of CLIL methodology positively impacted reading comprehension, improved communication, and improved motivation to learn, so teachers must use this approach in the English classes.